Extended hypoxia‐mediated H2S production provides for long‐term oxygen sensing. (18th September 2019) - Olson, Kenneth R.; Gao, Yan; DeLeon, Eric R.; Markel, Troy A.; Drucker, Natalie; Boone, David; Whiteman, Matt; Steiger, Andrea K.; Pluth, Michael D.; Tessier, Charles R.; Stahelin, Robert V.
Abstract: Aim: Numerous studies have shown that H2 S serves as an acute oxygen sensor in a variety of cells. We hypothesize that H2 S also serves in extended oxygen sensing. Methods: Here, we compare the effects of extended exposure (24‐48 hours) to varying O2 tensions on H2 S and polysulphide metabolism in human embryonic kidney (HEK 293), human adenocarcinomic alveolar basal epithelial (A549), human colon cancer (HTC116), bovine pulmonary artery smooth muscle, human umbilical‐derived mesenchymal stromal (stem) cells and porcine tracheal epithelium (PTE) using sulphur‐specific fluorophores and fluorometry or confocal microscopy. Results: All cells continuously produced H2 S in 21% O2 and H2 S production was increased at lower O2 tensions. Decreasing O2 from 21% to 10%, 5% and 1% O2 progressively increased H2 S production in HEK293 cells and this was partially inhibited by a combination of inhibitors of H2 S biosynthesis, aminooxyacetate, propargyl glycine and compound 3. Mitochondria appeared to be the source of much of this increase in HEK 293 cells. H2 S production in all other cells and PTE increased when O2 was lowered from 21% to 5% except for HTC116 cells where 1% O2 was necessary to increase H2 S, presumably reflecting the hypoxic environment in vivo. Polysulphides (H2 Sn, where n = 2‐7), the key signalling metabolite of H2 S also appeared to increase in many cells although this was often masked by high endogenous polysulphide concentrations. Conclusion: These results show that cellular H2 S is increased during extended hypoxia and they suggest this is a continuously active O2 ‐sensing mechanism in a variety of cells.